Are We Giving Optimal Dose of Efavirenz? - Evy Yunihastuti (Interna Publishing, 2016)
Antiretroviral is one of the drugs that extensively been studied for its drug-to- drug interaction. Its long term used and the fact that many HIV-infected patients came in the late stage of disease make polypharmacy is unavoidable. Efavirenz is one of antiretroviral drugs that widely used in HIV-infected patients age more than 3 years old in many countries. Latest Indonesian antiretroviral guidelines recommend a combination of tenofovir, lamivudine and efavirenz given orally in one daily dose as the  preferred  primary  fixed-drug  combination treatment. This recommendation is based on many evidence supporting efficacy, tolerability, price, pregnancy safety, simplicity and the availability of the drug that will support the continuing comprehensive care for HIV-infected patients in primary care level.